EVALUASI BENTUK DAN FUNGSI POHON PADA LANSKAP JALAN VETERAN KOTA MALANG, JAWA TIMUR - Rizki Alfian; Hesti Triana Soelistyari (Universitas Tribhuwana Tunggadewi, 2021)
This study aimed was to identify and evaluate the shape and function of trees, using a survey method with quantitative parameters, namely pollution reduction, noise suppression, and physical barrier. The parameters are adjusted to the criteria for the function of road landscape plants as determined by the Ministry of Public Works, Directorate General of Highways (1996). The existence of plants in the green lane of the Veterans Road landscape has an important meaning in relation to the security, safety, and comfort of road users and the sustainability of the surrounding environment. Based on the results of the evaluation carried out, it can be concluded that the quantity and quality of plants on the site from the aspect of their function as pollution reducers, noise absorbers, and space dividers, and aesthetic aspects have not fully met the criteria. Pollution reducing parameters, on the east side 73.8%; Central Park 86.46%; and West 75.36%, with a level of good to very good. As a noise reducer, plants in the East 50.5%; Central Park 45.65%; and West 61.65%, with moderate to good levels. As a Barrier, on the East side 66.00%; Central Park 64.2%; and West 63.00%, with good levels. As for aesthetics in the selection of plants, on the East side 22.89%; Central Park 25.35%; and West 17.74%, with poor grades. The crop arrangement on the East side is worth 76.8%; Central Park 87.36%; and West 74.22%, with a level of good to very good.